(untitled) (International Journal of Nursing Education, 2021)
Background: Mental health cadresholdthe pinpoint roles in the implementation of all mental health programs, both at sub-district and village levels. Objectives: Analyzing the roles of health cadres in the implementation of mental health programs at the health center in Aceh, a province in Indonesia. Research Method: The research method that will be used is observational, using the cross sectional design.All included people in this study are all cadres who reside in the district of Aceh Besar, Aceh province. The sample was using a total sampling technique of 584 cadres. Result: It was found that there was a relationship betweenacadre’s education with the role of a cadre in the implementation of mental health programs in the working area of the health centre in the district of Aceh Besar, Aceh province (p≤0,05). It was found that the relationship between training, knowledge, attitude, facilities and supervision with the role of a cadre in the implementation of mental health programs in the working area of the health centres in the district of Aceh Besar (p≤0,05). The most influencing variable or the most dominant variable that influences the role of a cadre in the implementation of mental health programs in the district of Aceh Besar is supervision. Conclusion: It can be concluded that supervision is the most dominating factor that influences the role of a cadre in the implementation of mental health programs in Aceh province’s health centre.